Consumer Culture, Taste Preferences, and Social Network Formation. Issue 6 (June 2015) - Puetz, Kyle
Abstract One of the most important and consistent findings in the social networks literature is that individuals are socially connected to people who resemble themselves. This finding extends to preferences for consumer culture. Whereas network theorists previously had presumed that social networks generated this outcome through a process of social influence, this traditional conception of the relationship between culture and social networks has been challenged by new theoretical perspectives and novel methodological techniques that enable researchers to empirically test the causal direction of the relationship. In this article, I first discuss how theorists have adjudicated between competing explanations of the relationship of taste preferences and social network structure. Second, I discuss how sociologists have theorized that tastes contribute to variation in network structure. Third, I examine survey and ethnographic research that discusses interactional mechanisms by which people actively mobilize culture to form social relationships. Fourth and finally, I discuss research that explores how consumer culture constitutes the meaning of social relationships and how relationship category affects theorizing of network formation.